THE PROBLEM OF ADAPTATION OF UKRAINIAN REFUGEES IN THE UK AND EU LABOUR MARKETS - Berveno, O.; Moskvina, A. (Municipal economy of cities. Series: «Economy science», 2024)
In February 2022, the escalating conflict in Ukraine led to a full-blown humanitarian crisis that has displaced more than 5.8 million refugees over the past two years. As of February 2023, more than 4.8 million Ukrainian refugees have registered in the European temporary protection system, with more than 2.1 million in the Eurozone (approximately 0.6% of the Eurozone population). Several Ukrainian research institutes are working on the issue of Ukrainian refugees abroad. International organisations and statistical authorities of receiving countries also pay considerable attention to the study of the Ukrainian wave of migration. However, despite the significant attention to this problem from scientists, it requires further analysis, both taking into account the rapid changes in certain aspects of life and the quantitative composition of Ukrainian refugees and from the point of view of the need for systematic consideration of research results for a deeper understanding of possible measures for the adaptation of forced migrants to local labour markets. The article aims to analyse the main prospects and difficulties of employing Ukrainian migrants abroad and obtaining additional skills and opportunities for their further return to Ukraine. Refugees are people who migrate to another country to escape war, violence, or other conflict or danger because they are unable or unwilling to return to their own country for fear of persecution or danger. A person becomes a refugee in the case of violation of their fundamental human rights or when they are under threat. Today, one of the highest refugee flows in the world is the Ukrainian wave of migration. Most Ukrainian refugees remain in Ukraine’s neighbouring countries: Poland has accepted 1.5 million refugees. The demographic composition of refugees from Ukraine differs from other refugee flows. In almost all host countries, at least 70% of the adult population are women, and more than a third of all refugees are women with children. Unlike previous refugee flows into Europe, newly arrived from Ukraine gained the right to seek work at a comparably early stage: the Temporary Protection Directive, which the EU launched in an unprecedented move at the beginning of March 2022, gives refugees from Ukraine the right to immediate employment and self-employment. Finding gainful employment that matches refugees’ educational and professional qualifications helps newly arrived become self-sufficient and stimulates the local economy. The data shows that Ukrainians account for 0.5% of the Eurozone workforce. As of February 2023, about 40% of Ukrainian refugees were employed or self-employed, corresponding to approximately half of all refugees working in Ukraine. However, a significant portion of primary employment concentrates on low-skilled jobs, and skills mismatch is a common problem for Ukrainian migrants. Insufficient language skills also hinder successful integration into the labour market.